Barriers and facilitators of complications risk perception among rural patients with type 2 diabetes mellitus: a qualitative content analysis - Zi-chen Zhang; Xiao-wei Wang; Shao-bo Li; Yu-qin Liu; Yu-min Li; Hong-Hong Jia (BMC Public Health)
Abstract Background Diabetes and its complications have emerged as a significant health threat to rural residents. Accurately perceiving the risk of complications may play a crucial role in modifying health behaviors and preventing complications’ occurrence. We aimed to explore the barriers to and facilitators of risk perception of complications in rural patients with type 2 diabetes mellitus, and to provide new perspectives and ideas for the development of relevant interventions in the future. Methods This study adopted the qualitative content analysis method. Semi-structured interviews were conducted with 14 rural diabetic patients selected by purposive sampling from July to September 2023, and the interview data were systematically analyzed. Results Data analysis identified 9 sub-themes falling into the 2 macro-themes: (a) facilitators of complications risk perception (Increased disease knowledge, Low sense of disease control, Risk experiences, Negative mindset); (b) barriers to complications risk perception (Lack of awareness of diabetes or its complications, Information barriers, Optimistic bias, Overconfidence, Disease generalization). Conclusions This study explored the barriers and facilitators of complication risk perception among rural patients with type 2 diabetes mellitus, offering new insights into risk perception research, and aiding primary medical staff to develop targeted intervention measures to ensure that rural diabetes patients can accurately and objectively perceive risk.